L'Accordo dell'Uruguay Round: una prima valutazione dei suoi effetti sull'UE e sui PSV - C. MASTROPASQUA; V. ROLLI (Moneta e Credito, 2013)
On December 15th of last year, seven years after its start, the Uruguay Round negotiations for the reform of the General Agreement on Tariffs and Trade came to a conclusion. This paper aims to provide a qualitative assessment of the results achieved in the fields of agriculture, market access, trade rules and intellectual property protection, leaving out services, given the limited results of liberalisation achieved in this area. In this limited context, the focus is on the European Union and developing countries. The authors describe the details of the agreement by sector before analysing the effects on the EU and developing countries. The effects of intellectual property protection both industrial countries and developing countries is then assessed.